Modeling the Dynamics of Money Income in Nigeria: a Co-Integration Approach - Omojimite, Ben U. (Mediterranean Journal of Social Sciences, 2011)
This study examined the relationship between real output, monetary aggregates, price, interest rate and exchange rate usingNigerian data. Analysis of the time series properties of the data revealed that the series are cointegrated which indicated that there is along- run relationship among the variables. We specified an error correction model to analyze the nature of relationship among thevariables. The data for the analysis were sourced mainly from the publications of the Central Bank of Nigeria. The result of theparsimonious model revealed that the error correction term of the broad money model came out with the right sign and significant, implyingthat a shock is rapidly (39%) accounted for in subsequent periods. A one period lag of real exchange rate and price has a negativerelationship with output and significant while M2 and interest rate are positively related to real output and also significant. The result ofthe variance decomposition analysis revealed that the Nigerian data supports the Monetarists’ explanations of business cycles andrecommends however that a combination of both monetary and fiscal policies be explored by the relevant authorities.